Existence and Uniqueness Results for Difference Î¦-Laplacian Boundary Value Problems - K. L. Bondar; V. C. Borkar; S. T. Patil (Institute for Research and Community Services (LPPM) ITB, 2011)
This paper is devoted to study the existence and uniqueness of solutions to nonlinear difference Î¦-Laplacian boundary value problems with mixed and Dirichlet boundary conditions.